2020
DOI: 10.7759/cureus.8639
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Protective Factors of the Prodromal Stage of Psychosis: A Literature Review

Abstract: Psychosis is a syndrome characterized by features of reality distortion such as delusions and hallucinations. It may occur as a primary mental disorder or secondary to a medical or neurological illness or substance abuse. Several genetic, environmental, and protective risk factors have been identified and require further study. Neurobiological damage at the onset of schizophrenia is the most active and destructive. Therefore, it is important to detect the prodromal phase of psychosis so that interventions can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Family history is considered one of the strongest risk factors for primary psychosis [16], with a heritability (i.e., the degree to which a phenotype, in this case a disorder, is genetically determined, calculated by regression-correlation analyses among close relatives) of schizophrenia estimated around 79-81% and a similar proportion in other disorders of the spectrum [17,18]. In particular, for close biologic relatives of patients with schizophrenia [13,19,20] was demonstrated a 7.5-fold higher risk for the development of primary psychosis [21] and studies on monozygotic twins [13,19,20] showed a concordance rate of approximately 50% [20,22].…”
Section: Individual Risk Factors Familiar and Parental Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Family history is considered one of the strongest risk factors for primary psychosis [16], with a heritability (i.e., the degree to which a phenotype, in this case a disorder, is genetically determined, calculated by regression-correlation analyses among close relatives) of schizophrenia estimated around 79-81% and a similar proportion in other disorders of the spectrum [17,18]. In particular, for close biologic relatives of patients with schizophrenia [13,19,20] was demonstrated a 7.5-fold higher risk for the development of primary psychosis [21] and studies on monozygotic twins [13,19,20] showed a concordance rate of approximately 50% [20,22].…”
Section: Individual Risk Factors Familiar and Parental Risk Factorsmentioning
confidence: 99%
“…As regards personality, many personality characteristics have been found to be implicated in the risk of developing primary psychosis, even though the majority of them showed a weak statistical association [15,16,24]. In particular, novelty seeking, harm avoidance, self-transcendence [15,24] and neuroticism [15,16] seem to increase the risk of developing primary psychosis, even if researchers agree that the most implied personality aspect is trait anhedonia [15,24].…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, prodrome is important for the diagnosis and treatment of schizophrenia (34). Therefore, several tools were created to detect the prodromal stage of psychosis (45). Intervention in the prodrome stage has been reported to improve cure rates and prognosis (46).…”
Section: Early Diagnosis Of Schizophreniamentioning
confidence: 99%